Selection Index (PSI) Method in Developing a Student Scholarship Decision Support System - Nur Arifin; Pujo Hari Saputro (Institut Teknologi Bisnis AAS Indonesia, 2022)
Scholarships are the provision of financial assistance for students or students with the aim that these students can continue their education that is being achieved. Decision Support System (DSS) is a system that can provide a problem or a communication capability for problems in unstructured and semi-structured conditions. The Preference Selection Index (PSI) method was developed by Maniya Bhatt (2010) to solve multiple decision criteria (MCDM). In the proposed method of weighting it is not necessary to assign relative importance between attributes, in fact, there is no need for attributes involved in decision making in this method. Compared to other MCDM methods, the PSI method is easier to reach because it involves fewer numerical calculations..